Pengaruh Inovasi Produk Terhadap Kinerja Pemasaran: Studi Kasus pada Brand Scarlett di Sashop Kota Gorontalo - Aziza Al-Hasni (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the influence of product innovation on marketing performance. The data used in this research is primary data, which was obtained from 85 respondents. This research uses Simple Linear Regression Analysis. The results of this research show that the Product Innovation Coefficient value is 1.401298 and the ρ (Prob) value for the variable is 0.0000. If the p-value is compared with the significance level, the p-value obtained is still smaller than the 0.01 significance level so that H0 is rejected. Thus, it can be concluded that Product Innovation has a positive and statistically significant effect on the Marketing Performance of the Scarlett Brand in Gorontalo City Sashop.